The effect of entertainment reality TV programs on value education for university youth: A field study on a sample of students at the University of Algeria 3 - Benmelit, Selma (Journal of Human Sciences, 2022)
This study aimed to identify the impact of pursuing entertainment reality TV programs on value education among university youth, and to reveal the relationship that exists between university youth exposure to these programs and the extent of the imbalance of value education for them, especially since the third world countries, including the Arab world, are still taking a position of amazement at what is happening around them Media materials are consumed twice as large as their absorptive capacity and their societies are flooded with a media flood that is not commensurate with their values, identity and the privacy of their societies, which is what made these countries consumer societies to receive media information only without strict media screening.